Municipal Human Development Index (IDHM) in2000 and 2010 in the microregion of Salinas - Northern Minas - Santos, Maria Ribeiro dos; Fonseca, Gildette Soares (Revista Cerrados, 2014)
The human development index (HDI) global is considered an excellent indicator of the living conditions of the population, as it aggregates the dimensions income, longevity and education. The Municipal Human Development index (IDHM) lets you know the level of development on a smaller scale, not necessarily meaning, that covers all points of interest. In this context, this study aims to analyze the IDH-M of the municipalities of Microregion of Salinas in 2000 and 2010, located in the Mesoregion of North of Minas. The methodological approach consisted in bibliographical research and prepared maps. The results showed evidence of low human development in Microregion of Salinas, although there have been improvements.